Large differences in education and training of radiographers in Europe and Central Asia: Results from an IAEA coordinated study. Issue 1 (February 2022) - Foley, S.; Paulo, G.; Vassileva, J.
Abstract: Introduction: Education and training of radiographers is known to be diverse between countries and regions. Under an IAEA project, this work collected data on radiographer education for the Europe and Central Asia region with a particular focus on radiation protection gaps and potential actions. Methods: Following piloting, an electronic questionnaire was distributed to all national counterparts for the IAEA Technial Coopearation (TC) Europe region (n = 33 countries) and nominated national representatives. Contacts were additionally invited to a virtual workshop to discuss and rank common problems in education and training of radiographers and to propose potential solutions. Results: Responses were received from 31 countries, including 14 from the European Union. Just over half of countries reported radiographer education being in higher education with 71% having program durations more than 3 years (range: 1 month-4 years). Programs included a spectrum of both clinical training and radiation protection hours with ten-fold variations noted across the region. Inclusion of core radiation protection topics within curricula varied similarly, as did radiographers' clinical involvement in both justification and optimisation between countries. Workshop participants identified five common training problems, namely education availability, lack of standardisation, radiation protection course quality, teamwork problems and lack of equipment. Conclusion: Radiographer education in the IAEA Europe region is heterogeneous with substantial differences in duration and quality of training programs between countries, which likely impact on quality of patient care delivered. Common problems have been identified and potential solutions proposed to focus quality improvement initiatives. Implications for practice: Radiographer education and training is diverse throughout the IAEA TC Europe region, with likely impacts on radiation protection practices applied. Clinical involvement of radiographers in justification and optimisation differs, potentially limiting adherence to radiation protection principles.